The Use of Sheep Movement Data to Inform Design and Interpretation of Slaughterhouse-Based Surveillance Activities - Stirling, Julie M.; Eze, Jude I.; Foster, Geoffrey; Reeves, Aaron; Gunn, George J.; Tongue, Sue C. (Frontiers in Veterinary Science, 2020)
The design of surveillance strategies is often a compromise between science, feasibility and available resources, especially when sampling is based at fixed locations, such as slaughter-houses. Advances in animal identification, movement recording and traceability should provide data that can facilitate the development, design and interpretation of surveillance activities. Here, for the first time since the introduction of electronic identification of sheep, the utility of a statutory sheep movement database to inform the design and interpretation of slaughter-house based surveillance activities has been investigated. Scottish sheep movement records for 2015-2018 were analysed, in combination with a number of other data sources. Patterns of off-farm movements of Scottish sheep to slaughter were described and the spatial distribution of several distinct slaughter populations, throughputs and catchment areas for Scottish slaughterhouses were determined. These were used to evaluate the coverage of a convenience-sample slaughter-house based survey for antimicrobial resistance (AMR). In addition, non-slaughter sheep movements within and between Scottish regions were described and inter-and intra-regional movement matrices were produced. There is potential for bias in spatially-associated factors for ovine surveillance activities based at Scottish slaughterhouses. This potential exists at a number of levels: when as in the AMR survey, the sampled sheep differ from the catchment area and/or the catchment area differs from the slaughtered in Scotland population and because –as demonstrated by the movement record analysis – the slaughtered in Scotland population differs from the overall Scotttish sheep slaughter population, The Scottish non-slaughter sheep population is dynamic. Inter-regional movements vary seasonally, driven by the sheep calendar year, structure of the Scottish sheep industry and management practices. These sheep movement data provide a valuable resource for surveillance purposes, despite a number of challenges and limitations that were encountered. They can be used to identify and characterize the spatial origin of relevant populations and so inform the interpretation of existing slaughterhouse-based surveillance activities. They can be used to improve future design by exploring the feasibility and cost:benefit of alternative sampling strategies. Further development could also contribute to other surveillance activities, such as situational awareness and resource allocation, for the benefit of stakeholders.